Evidence for a bottom-light initial mass function in massive star clusters. Issue 3 (1st March 2023) - Baumgardt, H; Hénault-Brunet, V; Dickson, N; Sollima, A
ABSTRACT: We have determined stellar mass functions of 120 Milky Way globular clusters and massive Large Magellanic Cloud/Small Magellanic Cloud star clusters based on a comparison of archival Hubble Space Telescope photometry with a large grid of direct N -body simulations. We find a strong correlation of the global mass function slopes of star clusters with both their internal relaxation times and their lifetimes. Once dynamical effects are being accounted for, the mass functions of most star clusters are compatible with an initial mass function described by a broken power-law distribution N ( m ) ∼ m α with break masses at 0.4 and 1.0 M⊙ and mass function slopes of αLow  = −0.3 for stars with masses m < 0.4 M⊙, αHigh  = −2.30 for stars with m > 1.0 M⊙, and αMed  = −1.65 for intermediate-mass stars. Alternatively, a lognormal mass function with a characteristic mass log  M C  = −0.36 and width σC  = 0.28 for low-mass stars and a power-law mass function for stars with m > 1 M⊙ also fit our data. We do not find a significant environmental dependence of the initial mass function on cluster mass, density, global velocity dispersion, or metallicity. Our results lead to a larger fraction of high-mass stars in globular clusters compared to canonical Kroupa/Chabrier mass functions, increasing the efficiency of self-enrichment in clusters and helping to alleviate the mass budget problem of multiple stellar populations in globular clusters. By comparing our results with direct N -body simulations, we finally find that only simulations in which most black holes are ejected by natal birth kicks correctly reproduce the observed correlations.